Do the self-employed still vote for centre-right parties? The cases of the UK, Italy and Spain. (April 2018) - Barisione, Mauro; De Luca, Deborah
Abstract: The disappearance of class voting in post-industrial societies has often been announced in recent decades. Few studies, however, have focused on the self-employed, an occupational category which tends to combine the properties of a social class and a status group. The UK, Italy, and Spain present different traditions but similar levels of class voting in the early 2000s, with a persisting tendency of the self-employed to vote for centre-right parties. These three countries also saw the subsequent growth of "third" parties. Using data on parliamentary elections from the 2004, 2009, and 2014 European Election Studies, we continue to find evidence of this form of class voting, which we relate to the specific political and social dispositions of the self-employed. But we also find a decline during the decade considered, which we impute to ideological convergence of the mainstream left and right parties along the fundamental "workers vs. owners" class cleavage.